Modelling integrated socio-technical feedback systems : e-democracy and other applications - Boufoy-Bastick, Zach-Amaury (University of Guyana. Department of Computer Science GeorgetownGY, 2005)
Uses analogies from political science to discuss and analyse the growth of virtual moderation, identifying the four developmental categories of a posteriori moderation, a priori moderation, team moderation external moderation or self-moderation.